2017
DOI: 10.1016/j.jhazmat.2017.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Ionomic and transcriptomic analysis provides new insight into the distribution and transport of cadmium and arsenic in rice

Abstract: To identify the key barrier parts and relevant elements during Cd/As transport into brown rice, 16 elements were measured in 14 different parts of 21 rice genotypes; moreover, transcriptomic of different nodes was analyzed. Cd/As contents in root and nodes were significantly higher than those other parts. Node I had the highest Cd content among nodes, leading an increase in gene expressions involved in glycolytic and Cd detoxification. The Cu/Zn/Co distribution and transport to various parts was similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 61 publications
(58 reference statements)
7
28
0
2
Order By: Relevance
“…Regarding to the interspecific relationships between elements in this work As and Cd were closely related to Cu, Fe and Mo. Regarding to their mobility, it was agree with the results reported by Feng, et al (2017), where Cd transport mechanisms also favored Cu, Zn and Mg translocations. According to Turgut, et al (2005), the FT is employed to evaluate the capacity of heavymetal transport from roots to shoots; in this study there was a particular association between elements with FT > 1, for Mn, Mg, Ca and Zn.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding to the interspecific relationships between elements in this work As and Cd were closely related to Cu, Fe and Mo. Regarding to their mobility, it was agree with the results reported by Feng, et al (2017), where Cd transport mechanisms also favored Cu, Zn and Mg translocations. According to Turgut, et al (2005), the FT is employed to evaluate the capacity of heavymetal transport from roots to shoots; in this study there was a particular association between elements with FT > 1, for Mn, Mg, Ca and Zn.…”
Section: Discussionsupporting
confidence: 92%
“…Williams and Salt (2009) noted that a balanced supply of these elements ensures an optimal plant growth and development, regulating their homeostasis. It is know that mineral elements interact with one another, according to their similarities in chemical properties and interrelated metabolic pathways (Patterson 1971;Feng, et al 2017). The development of ionomics contributes to explore interactions between them (Salt 2004;Lyubenova, et al 2013;Chu, et al 2015) and this strategy evaluates their adsorption and accumulation in plants by an elemental analysis (Salt 2004).…”
Section: Introductionmentioning
confidence: 99%
“…macro-and micro-nutrients, other topics such as biofortification of harvest products for increasing their nutritional value (JEŽEK et al, 2011) or controlling the uptake of toxic elements such as heavy metals have important implications in food science and animal nutrition. Thus, a broader understanding of heavy metal ionomics is essential for coping with farmland pollution and for maintaining a high level of food safety (SINGH et al, 2016;FENG et al, 2017).…”
Section: Ionomics Of Soybean Cadmium Accumulationmentioning
confidence: 99%
“…Studies have shown that node is a pivotal location for nutrient distribution in graminaceous plants [12]. Both root and node are key barriers to Cd transport into rice grains [13]. Node is a central organ for xylem-tophloem transfer of nutrients, ions, and metabolites [12].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic manipulation of the transporters in stem-portion might prevent the distribution of toxic heavy metals, like Cd, into grains [15]. Feng et al (2017) reported that the Cd concentration profiles were distinct in different part of rice, including stem nodes [13]. They showed that node I had higher capacity in Cd sequestration and detoxification, and node I had higher expression of genes associated with glycolysis and detoxification.…”
Section: Introductionmentioning
confidence: 99%